Thinking about the construction of university town from the public bicycle travel of college students: A Chinese empirical study. (January 2023) - Qin, Xiao; Zhen, Feng; Guo, Suping; Tang, Jia
Highlights: The time–space travel analysis of College Students' public bicycles is the key to guide the construction of University City. Travel area is related to the campus layout and the number of surrounding commercial facilities, railway stations or bus stops. Travel time period is related to the number of surrounding public facilities or bus stops. Travel duration is related to the campus layout and the number of surrounding public facilities or bus stops. Abstract: At present, scholars have mostly discussed urban residents' public bicycle travel behaviour and the effect of built environment; however, relevant research on college students is insufficient, and a thinking path for the construction of university towns is lacking. On the basis of questionnaire survey and point-of-interest data and taking Xianlin University Town in Nanjing, China as an example, this paper focuses on the spatiotemporal characteristics of college students' public bicycle travel and the influencing factors of its built environment. Results of multiple logistic regression model show that (1) travel area is related to the campus layout and the number of surrounding commercial facilities, railway stations or bus stops. (2) Travel time period is related to the number of surrounding public facilities or bus stops. (3) Travel duration is related to the campus layout and the number of surrounding public facilities or bus stops. Finally, this paper proposes some suggestions from the aspects of space optimisation layout of public bicycle stations and vehicle space–time scheduling, campus internal space function adjustment and public service facility construction.